Adherence to the Eatwell Guide and associations with markers of physical function: a prospective analysis within the UK Biobank cohort - Alex Griffiths; Sarah Gregory; Fiona C. Malcomson; Kirstie Cronin; Jamie Matu; Louisa Ells; Oliver M. Shannon (GeroScience, 2026)
The Eatwell Guide represents the UK’s principal healthy eating model and understanding whether adherence to UK dietary recommendations can attenuate age-related functional decline is essential to inform healthy ageing strategies. In up to 157,457 participants from the UK Biobank, we explored cross-sectional and prospective associations between adherence to the Eatwell Guide and markers of physical function (grip strength, fat-free mass percentage, self-reported walking pace, and falls). Eatwell Guide adherence scores were derived from 24-h dietary recall data (Oxford WebQ), and quantified using a graded, food-based scoring system. Differences between population subgroups including by age, sex, physical activity, and protein intake level were explored. Higher Eatwell Guide adherence was cross-sectionally associated with higher grip strength, greater fat-free mass percentage, higher odds of brisk walking pace, and lower odds of falls (all p < 0.001). Prospectively, greater adherence was associated with attenuated fat-free mass decline (β = 0.02, SE = 0.001, p < 0.001) and slower grip strength decline (β = 0.01, SE = 0.002, p < 0.01). For walking pace, the positive cross-sectional association attenuated over follow-up (EWG × time interaction OR = 0.998, 95% CI 0.997–0.999, p = 0.002), whereas the protective association with falls remained stable over time (OR = 1.000, 95% CI 0.998–1.000, p = 0.89). Higher Eatwell Guide adherence was associated with preserved muscle mass, modest attenuation of grip strength decline over time, and a reduced risk of falls, supporting its relevance for musculoskeletal health and physical function in aging populations.

Effects of dietary nitrate supplementation on oral health and associated markers of systemic health: a systematic review - Shatha S. Alhulaefi; Anthony W. Watson; Sheena E. Ramsay; Nick S. Jakubovics; Jamie Matu; Alex Griffiths; Rachel Kimble; Mario Siervo; Kirsten Brandt; Oliver M. Shannon (Critical Reviews in Food Science and Nutrition, 2025)

Effects of a mediterranean diet on the gut microbiota and microbial metabolites: A systematic review of randomized controlled trials and observational studies - Rachel Kimble; Phebee Gouinguenet; Ammar Ashor; Christopher Stewart; Kevin Deighton; Jamie Matu; Alex Griffiths; Fiona C. Malcomson; Abraham Joel; David Houghton; Emma Stevenson; Anne Marie Minihane; et al. (Critical Reviews in Food Science and Nutrition, 2023)

Substrate oxidation and the influence of breakfast in normobaric hypoxia and normoxia - Alex Griffiths; Kevin Deighton; Oliver M. Shannon; Jamie Matu; Roderick King; John P. O’Hara (European Journal of Applied Physiology, 2019)

Collision activity during training increases total energy expenditure measured via doubly labelled water - Nessan Costello; Kevin Deighton; Thomas Preston; Jamie Matu; Joshua Rowe; Thomas Sawczuk; Matt Halkier; Dale B. Read; Daniel Weaving; Ben Jones (European Journal of Applied Physiology, 2018)

Changes in appetite, energy intake, body composition, and circulating ghrelin constituents during an incremental trekking ascent to high altitude - Jamie Matu; John O’Hara; Neil Hill; Sarah Clarke; Christopher Boos; Caroline Newman; David Holdsworth; Theocharis Ispoglou; Lauren Duckworth; David Woods; Adrian Mellor; Kevin Deighton (European Journal of Applied Physiology, 2017)
Purpose Circulating acylated ghrelin concentrations are associated with altitude-induced anorexia in laboratory environments, but have never been measured at terrestrial altitude. This study examined time course changes in appetite, energy intake, body composition, and ghrelin constituents during a high-altitude trek. Methods Twelve participants [age: 28(4) years, BMI 23.0(2.1) kg m −2 ] completed a 14-day trek in the Himalayas. Energy intake, appetite perceptions, body composition, and circulating acylated, des-acylated, and total ghrelin concentrations were assessed at baseline (113 m, 12 days prior to departure) and at three fixed research camps during the trek (3619 m, day 7; 4600 m, day 10; 5140 m, day 12). Results Relative to baseline, energy intake was lower at 3619 m ( P = 0.038) and 5140 m ( P = 0.016) and tended to be lower at 4600 m ( P = 0.056). Appetite perceptions were lower at 5140 m ( P = 0.027) compared with baseline. Acylated ghrelin concentrations were lower at 3619 m ( P = 0.046) and 4600 m ( P = 0.038), and tended to be lower at 5140 m ( P = 0.070), compared with baseline. Des-acylated ghrelin concentrations did not significantly change during the trek ( P = 0.177). Total ghrelin concentrations decreased from baseline to 4600 m ( P = 0.045). Skinfold thickness was lower at all points during the trek compared with baseline ( P ≤ 0.001) and calf girth decreased incrementally during the trek ( P = 0.010). Conclusions Changes in plasma acylated and total ghrelin concentrations may contribute to the suppression of appetite and energy intake at altitude, but differences in the time course of these responses suggest that additional factors are also involved. Interventions are required to maintain appetite and energy balance during trekking at terrestrial altitudes.